Grubbs‐inspired metathesis in the Moore group. Issue 18 (13th April 2017) - Moneypenny, Timothy P.; Liu, Huiying; Yang, Anna; Robertson, Ian D.; Moore, Jeffrey S.
ABSTRACT: Alkene metathesis has proven to be a powerful method for carboncarbon bond formation, particularly in the field of polymer and materials science. The availability of various tailor‐made catalysts not only enables the synthesis of well‐defined polymers but facilitates the development of functional, stimuli–responsive materials. This highlight, dedicated to Professor Robert Grubbs on his 75th birthday, focuses on the various research efforts in our group utilizing both alkene and alkyne metatheses and the interesting materials derived from them. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2935–2948 Abstract : Polymer and materials science has significantly benefited from fundamental advances in olefin metathesis. The commercially available assortment of well‐defined, highly active ruthenium metathesis catalysts enables the synthesis of functional macromolecules with controlled architectures and narrow molecular weight distributions. This highlight article, dedicated to Professor Robert Grubbs' 75th birthday, discusses research efforts involving both olefin and alkyne metatheses with particular emphasis on inspiration garnered from Prof. Grubbs' ideology.